Carbetocin and Oxytocin in the Active Management of third Stage of Labor after Vaginal Birth of Baby - Barua, Hena Rani; Barua, Rita Rani; Barua, Sushanta; Barua, Ajoy Kishore; Begum, Kohinoor (Bangladesh Medical Journal, 2017)
Postpartum hemorrhage (PPH) is one of the major contributors to maternal mortality and morbidity worldwide. Active management of the third stage of labor has been proven to be effective in the prevention of PPH. Carbetocin; a long-acting Oxytocin agonist appears to be a promising agent for the prevention of PPH. In this study Carbetocin is used for the active management of third stage of labor to prevent PPH. Two hundred pregnant women from July 2015 to December 2015 at Rangamati Medical College Hospital, Rangamati, Bangladesh were included in this study. The patients were divided into two groups: Group- 1 (100 women) were received 100μg Carbetocin intravenously and group- 2 (100 women) received 10 IU Oxytocin intramuscularly and both doses were single. These uterotonics were injected at anterior shoulder after the delivery of the baby. Significant difference was observed between the Carbetocin and Oxytocin receiving groups regarding amount of blood loss (335.70 ± 117.71 versus 375.12 ± 145.30), PPH (3 % versus 12%), need of use of other uterotonics (18% versus 30%) and the difference in hemoglobin percent before and after delivery (0.58 ± 0.34 versus 0.97± 0.52). All these parameters were lower in Carbetocin group except hemoglobin level which is higher in group- 2 during 24 hours after delivery. Moreover, blood transfusion was not indicated in group- 1. In conclusion, Carbetocin is superior to Oxytocin in prevention of post partum hemorrhage at the third stage of vaginal delivery with minimal homodynamic changes and side effects. Bangladesh Med J. 2017 Jan; 46 (1): 7-10